2018
DOI: 10.1002/apj.2273
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high temperature oxidation on molecular structure and performance of aviation base oils

Abstract: In this paper, the dioctyl adipate (DIOA) and poly‐α‐olefin (PAO) were comparatively study to systematic evaluate the influence of high temperature oxidation on the molecular structure and performance of the base oil. Even the DIOA has better antioxidation properties, antioxidant could significantly reduce the molecular structure damage during high temperature oxidation for the both two kinds of base oils. Because the decrement of kinematic viscosity was slow down after antioxidant was added into the base oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Colorimeter has a long history for measuring the quality of the refined petroleum products since 1933 [7][8][9] , which also suggests the color is an important parameter of aviation lubrication oils. As reported by the previous study [10][11][12] , the molecular structure change and the properties deterioration of the oxidized oil samples are confirmed, which also result in gradually changing of the oxidized oil samples color. However, the intrinsic relationship between the oil molecules (oxidizing products and antioxidants) and the resulting color variation needs to be established which could develop a fast and low-cost strategy to rapidly estimate the oil quality.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Colorimeter has a long history for measuring the quality of the refined petroleum products since 1933 [7][8][9] , which also suggests the color is an important parameter of aviation lubrication oils. As reported by the previous study [10][11][12] , the molecular structure change and the properties deterioration of the oxidized oil samples are confirmed, which also result in gradually changing of the oxidized oil samples color. However, the intrinsic relationship between the oil molecules (oxidizing products and antioxidants) and the resulting color variation needs to be established which could develop a fast and low-cost strategy to rapidly estimate the oil quality.…”
supporting
confidence: 79%
“…The T531 also has similar effect on color change with T501, although in different base oils. Interestingly, the oxidized PAO oil sample which added 1% Tz516 and 1% T501 (P516/501) has lower color number (0-12) compared with the color number (11)(12)(13)(14) of PAO oil sample with 1% Tz516 (P516). Especially under shorter oxidation time, the color number of P516/501 is 0 after oxidizing for half an hour while the color number of P516 is 11.…”
Section: Hosted Filementioning
confidence: 99%
“…Sliding against a 440C steel ball would press out the residual nanoparticles from the PG-PPI surface, causing three-body abrasive wear and degenerate lubrication properties. Previous research found that the degradation of PAO oil at high temperatures contributes significantly to the blackening phenomenon. The three-body contact increases the local contact stress and creates a high flash temperature, which is thought to be the primary source of more black products on the PG-PPI surface (Figure c) or the Al 2 O 3 abrasive particles added CP-PPI surface (Figure b).…”
Section: Discussionmentioning
confidence: 97%